Building Performance Through Work Discipline Influenced by Work Environment and Compensation - Hudaya, Agung; Jubaedah; Sugiharjo, R. Joko; Paijan, Paijan (Journal of Sustainable Economic and Business, 2024)
Objective: The objectives of this study are. To determine the effect of work environment variables and rewards on employee performance through employee work discipline through work discipline. To determine whether there is a direct and indirect effect of work discipline intervention variables, in order to determine performance improvement strategies in the organization. Methodology: This study refers to quantitative research by collecting a sample of 110 respondents, then through the data processing process using smart PLS. Results of the study: The results of the study indicate that there is an influence given by the work environment on performance, compensation variables affect performance, work discipline affects performance, the results of indirect effects also show that there is an influence given by the work environment on performance through work discipline and the influence given by the work environment on performance through work discipline. Conclusion: The results show that the work environment has an influence on performance, compensation for performance, directly and indirectly through work discipline, and work discipline has a significant influence on performance.